2017
DOI: 10.3892/mco.2017.1146
|View full text |Cite
|
Sign up to set email alerts
|

Rare giant primary ureteral polyp: A case report and literature review

Abstract: Primary ureteral fibroepithelial polyps (UFPs) are rare benign tumors of mesodermal origin. The majority UFPs are observed in the proximal part of the ureter and most commonly on the left side. The mean diameter of UFP is reported to be <5 cm. We herein present a rare case of a long primary ureteral polyp originating from the lower ureter in a 53-year-old woman. Following computed tomography, magnetic resonance imaging, retrograde pyelography and ureteroscopic examination, a preliminary diagnosis of giant prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Both CECT KUB and MRI KUB are inadequate modalities when it comes to differentiating FEPs from UCC, and management decisions should not be solely based on imaging findings. 1,5 The moth-eaten appearance usually described for UCC may also be seen with FEPs, as in our case, as opposed to the smooth filling defect usually described. 3 This emphasizes the importance of careful ureteroscopic examination before any ablative procedure is undertaken.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Both CECT KUB and MRI KUB are inadequate modalities when it comes to differentiating FEPs from UCC, and management decisions should not be solely based on imaging findings. 1,5 The moth-eaten appearance usually described for UCC may also be seen with FEPs, as in our case, as opposed to the smooth filling defect usually described. 3 This emphasizes the importance of careful ureteroscopic examination before any ablative procedure is undertaken.…”
Section: Discussionsupporting
confidence: 63%
“…These benign mesenchymal tumours account for <1% of all genitourinary neoplasms. 1 FEPs are usually described in the left proximal ureter (70%) with a male preponderance (58–89%), 2,3 and distal ureteral giant primary FEPs are extremely rare. The median length of FEPs described in the literature is 4 cm (4–17 cm).…”
Section: Introductionmentioning
confidence: 99%
“…Kijvikai et al ( 7 ) reported a case with a 17-cm-long FEP stemming from a distal UPJ, which was treated with laparoscopic pyeloplasty. Recently, endoscopic treatment has been used with increasing frequency for patients with ureteral tumors, as seen in the present case ( 8 ). Open or laparoscopic/robotic treatment options may be available for surgeons who lack sufficient experience for endoscopic treatment ( 9 ).…”
Section: Discussionmentioning
confidence: 78%
“…Comparison with the adult population [12,14,29,30] indicates that the clinical presentation of FEP appears to be similar. The management, however, is not entirely the same.…”
Section: Discussionmentioning
confidence: 91%